The Second All-Russian Scientific and Practical Conference «Issues of Radiation, Chemical and Biological Protection in Peacetime and Wartime» - Константин Николаевич Аккузин; Иван Анатольевич Сырников; Наталья Игоревна Шило (Вестник войск РХБ защиты)
.